Numerical simulation and experimental verification of a small refrigerated warehouse with PCM plates. (November 2022) - You, Hui; Sun, Jintao; Xie, Jing
Abstract: In this paper, phase change materials (PCM) plates are placed in cold store to use their latent heat to store cold and slow down the rise in temperature in the store, thus extending the shelf life of food products. Five kinds of PCM for cold storage were obtained by compounding several organic and inorganic solutions. The properties of phase change temperature, latent heat of phase change and subcooling were integrated, and a B composite solution consisting of 30% ammonium bromide, 10% ammonium chloride, 1% strontium dioxide, 5% xanthan gum and 54% water was recommended for -18 °C cold storage. Cold storage plates encapsulated B composite solution and placed on top of the storage. The temperature of the cold storage with PCM plates rose to -10 °C in 217 min, which was delayed near 2 h compared to the cold store without PCM plates. Meanwhile, a physical–mathematical model was developed and the temperature field of the cold store with PCM plates was simulated by computational fluid dynamics (CFD). The results showed that the temperature reached -10 °C in 215 min with an error of 2.2% compared to the experimental results, and the simulation results were reliable. It is shown that it is feasible to use numerical simulation to analysis the temperature field of the actual cold storage, and it provides a reference for the subsequent research of cold storage. For the PCM plates designed for 6 h of cold storage, the final storage time was 2 h. Subsequent research can be carried out on refrigerated warehouse with PCM plates with good insulation performance; the PCM plates will be cooled using the refrigeration unit to increase the heat transfer temperature difference. The use of a thinner thickness of the PCM plates, the fan of the refrigeration system is turned on to strengthen the heat exchange.